IMPLEMENTASI PEMBELAJARAN GHARIBUL QUR’AN DALAM METODE UMMI UNTUK MENINGKATKAN KUALITAS BACAAN QUR’AN PADA SANTRI - Muhammad Abdul Rahim; Zahroh Firdausi; Happy susanto; Anip Dwi Saputro (LPPM IAD Probolinggo, 2025)
Implementation of Gharibul Qur'an in Ummi Method to Improve the Quality of Qur'an Reading in Students of Madrasah MI Mambaul Huda Al-Islami'yah Wali Songo Ngabar Ponorogo. It is very important because Al-Qur'an education improves the quality of faith and good morals. This study aims to: determine the planning, implementation, and evaluation and results of the actions of the teachers and coordinators so that learning can run well so that the quality of reading students increases and becomes better. To achieve these results, the researcher used a qualitative method. With the location at MI Mambaul Huda Al-Islamiyah. As the source from the teachers. With observation, interview, and documentation collection techniques. The results of the research that has been carried out have obtained results which reveal that: 1. The planning of the Ummi Gharibul Qur'an method has been well structured, the planning components are good, and the quality of the teachers is a determinant of success. The Ummi method that has been implemented has been in accordance with what is required. 2. The implementation that runs clearly from the beginning to the end of the stage, time, and supporting tools for learning success are good. All learning is in accordance with existing theories so that the quality of learning is good and well structured to achieve good reading quality for students. 3. The evaluation results are clear and structured to measure student understanding, the actions taken by teachers provide motivation, and a teacher must also strive to improve the quality of a teacher to become even better. So the quality of children's reading ultimately improves, which can be proven by the munaqosah and khataman activities held annually. Keywords: Gharibul Qur'an, Ummi Method, Improving the Quality of Qur'an Recitation